Analysis of pharmacovigilance databases for spontaneous reports of adverse drug reactions related to substandard and falsified medical products: A descriptive study - Pozsgai, Kevin; Szűcs, Gergő; Kőnig-Péter, Anikó; Balázs, Orsolya; Vajda, Péter; Botz, Lajos; Vida, Róbert György (Frontiers in Pharmacology, 2022)
Introduction The public health threat of substandard and falsified medicines is well known in the last two decades, and several studies focusing on identification of products affected and preventing the consumption have been publishing. However, the number of these products reaching patients and causing health consequences and Adverse Drug Reactions is not a well-researched area. Objectives Our aim was to identify and describe the characteristics of cases that are related to Adverse Drug Reactions potentially originated from counterfeit medication using publicly available Pharmacovigilance data. Methods A descriptive study was performed based on pharmacovigilance data retrieved from Individual Case Safety Reports (ICSR) identified in the European Medicines Agency EudraVigilance and FDA Adverse Event Reporting System (FAERS) databases in April 2022 using selected MedDRA Preferred Terms counterfeit product administered, product counterfeit, product label counterfeit, product packaging counterfeit, suspected counterfeit product, adulterated product, product tampering, suspected product tampering. ICSRs were analyzed by age and gender, by year of reporting, region of origin, reporter’s profession, and severity of outcome. The disproportionality method was used to calculate pharmacovigilance signal measures. Results A total of 5253 cases in the FAERS and 1049 cases in the EudraVigilance database were identified, generally affecting middle-aged men with a mean age 51.055 (±19.62) in the FAERS and 64.18% of the cases between 18 and 65 years, while the male to female ratios were 1.18 and 1.5. In the FAERS database we identified 138 signals including sildenafil (n=314; PRR, 12.99; ROR, 13.04; RRR, 11.97), tadalafil (n=200; PRR, 11.51; ROR, 11.55; RRR, 10.94) and oxycodone (n=190; PRR, 2.47; ROR, 2.14; RRR, 2.47. While in the EV data 31, led by vardenafil (n=16, PRR=167.19, RRR=, ROR= p< 0.001), entecavir (n=46, PRR=161.26, RRR=154.24, ROR=163.32, p<0.001) and tenofovir (n=20, PRR=142.10, RRR= 139.42, ROR=143.74, p<0.001) Conclusion The application of pharmacovigilance datasets to identify potential counterfeit medicine ADRs can be a valuable tool in recognition of potential risks groups of consumers and the affected active pharmaceutical ingredients and products. However, the further development and standardization of ADR reporting, Pharmacovigilance database analysis and prospective and real-time collection of potential patients with health consequences is warranted in the future.